Review Essay: Lacan, via Messenger - Achim Seiffarth (Forum: Qualitative Social Research, 2006)
We'll never know what LACAN really said. The various editions of his works are only partly authorized by LACAN himself, and the few critical editions are not among those that are. Anyone who wants to learn about the Master's thought has to study influences, transmissions, and the trajectories of words and texts ascribed to LACAN. The contributors to this volume by THOLEN, SCHMITZ and RIEPE focus on the three themes nominated in the book's title. Some primarily discuss the role of transfer in psychoanalysis, others critically examine German translations of the Master's texts, and a third group studies the emergence of a psychoanalytic tradition. We might affirm that all the articles represent the three T's together: practising transfer, translating what might otherwise be incomprehensible, and constituting tradition. But this is a bond too weak to connect the various works presented in THOLEN, SCHMITZ and RIEPE's book. In fact, the book seems to explode. The range of topics treated by the authors reaches far beyond any disciplinary border and includes themes as different as dysgraphia and dyslexia, interpretations of HÖLDERLIN, BENJAMIN and KAFKA, the legal definition of death, theory of mass communication, the history of psychology, and the diffusion of psychoanalysis in Europe (Italy, Austria, Belgium and Ireland). As a consequence, reading the mostly well written and stimulating articles one after the other might be slightly irritating. "Transfer—Translation—Tradition" is an interesting book, though it's not really a book at all. This kind of successful failure probably is LACANian heritage (even if, yes, we've heard that story from Bob DYLAN, too). URN: urn:nbn:de:0114-fqs0603156